MICROBIOLOGICAL SUBSTANTIATION OF DRUG COMPOSITION WITH ARGININE FOR THE TREATMENT OF PATIENTS WITH PERIODONTAL DISEASE - A.S. Kuvayev; A.V. Borysenko; A.V. Viderskaya; A.L. Liesnykhina (Bogomolets National Medical University, 2016)
Urgency. For a complex treatment of patients with generalized periodontitis using various antimbacterial (antiseptics, antibiotics, antifungal and antiprotozoal drugs), anti-inflammatory drugs, calcium supplements, antiresorbtive and others. Today, among these drugs attract the attention of medicaments affecting the metabolism of nitric oxide. For clinical use it has been proposed pharmacological composition containing cardioarginin. Before clinical usage of this composition, it was important to investigated its antibacterial action. Aim. To determine the antibacterial action of the proposed pharmacological composition to the standard strains of microorganisms and mixed microflora of periodontal pockets. Materials and methods. To determine the antibacterial activity were selected standard strains of microorganisms and mixed microflora of periodontal pockets of patients with generalized periodontitis. To determine antimicrobial effect using agar diffusion method ("wells" method). Results. Pharmacological composition X showed no significant antibacterial properties. Metrogil denta had an effect on all microorganisms, with the appearance of a low sensitivity to the drug. The study pharmacological composition M has shown the most impressive antibacterial effect on standard strains of microorganisms and mixed microflora of periodontal pockets of patients with generalized periodontitis. Conclusions. The high anti-bacterial effect of the modified drug formulation with respect to the mixed microflora of periodontal pockets gives reason for its use in treatment of patients with generalized periodontitis.